Avaliação do impacto da colmatação e de métodos de descolmatação em wetlands construídos de escoamento horizontal subsuperficial - Gabriel Rodrigues Vasconcellos (2020)
Clogging in constructed wetlands causes hydrodynamic, aesthetic, and even system´s performance problems. There are thousands of units implemented around the world and the main concern of this type of system is related to clogging the bed, which is an inevitable process over the time. The horizontal subsurface-flow constructed wetlands (HSCW), among wetland variants, are the ones that most face clogging problems. This type of system is mainly designed to remove organic matter and solids suspended in wastewater. Many units, despite of having serious clogging problems, still perform satisfactorily in terms of removal of organic matter and solids, even though operating in critical conditions, with surface-flow and close to a severe deterioration, here characterized as an operational “collapse” (in hydrodynamic terms and in the purification capacity). Based on it, this work aims to evaluate the impact of the clogging and inferring about a possible “collapse” in performance, and of unclogging methods in two constructed wetlands with horizontal subsurfaceflow, being one unit planted with cattail (Typha latifolia) and the other one unplanted. The two units operate in parallel, each one with a population equivalent of, approximately, 50 inhabitants, receiving a continuous flow of about 7.5 m³ d-1 , most of the time. Each unit is 25 m long and 3 m wide and both were filled with 0.40 m of blast furnace slag. At this study were evaluated data generated in, approximately, 12 years and 8 months of monitoring, from the beginning of the operation to the high degree of the system´s clogging, in addition to the implementation of two types of bed unclogging methods. Most of the time, since June 2007, the system received municipal sewage previously treated in a UASB type reactor and, during a specific period, received effluent from a percolator biological filter operating as a post-treatment of UASB reactor effluent. In addition to the change in the type of pre-treatment, the increase in the influent load on the system's performance was also evaluated. The influent of the units has a median, for the entire period evaluated, of 59 mgBOD L -1 , 139 mgCOD L -1 and 45 mgTSS L-1 , resulting in application rates in the cross section of 373 and 408 gDBO m-2 d -1 , 982 and 1020 gDQO m-2 d -1 , 269 and 237 gTSS m-2 d -1 , for the planted and unplanted units, respectively. During most of the operational period, the performance of both units was satisfactory with median effluent concentrations of 20 and 19 mgBOD L -1 , 48 and 54 mgCOD L -1 and 12 and 8 mgTSS L-1 (planted unit and unplanted unit, respectively), although evidence of clogging (surface flow) was observed in the second year of operation. The clogging of the beds was observed from the second year of operation, leading to surface flow and accumulation of sludge on the surface. The impact on system´s performance was assessed using Statistical Process Control (SPC). The result of the SPC indicated that the system´s Programa de Pós-graduação em Saneamento, Meio Ambiente e Recursos Hídricos da UFMG collapse, in terms of performance, that is when the quality of the effluent was no longer in normal operating conditions, started in the first years of operation and was the result of the advance of the clogging in the beds. Nevertheless, the quality of the effluent in both units was according to the local discharge standards. The upstream treatment of the wetlands and the load applied to the bed influenced the system´s performance, more than the period of operation itself, showing the robustness of the HSCW. Based on it, unclogging methods were evaluated in undisturbed samples of the beds and in real scale of the planted and unplanted units. In undisturbed samples the resting period of 7, 14 and 30 days were evaluated, washing of the support medium and application of hydrogen peroxide in doses of 172, 1039 and 1847 mL of 35% H2O2. The results of the tests with undisturbed samples indicated that all the evaluated methods were promising for application in real scale. For simplicity reasons, the rest period of and application of hydrogen peroxide were chosen to be applied to the beds. In the planted unit, 2,000 liters of hydrogen peroxide were applied, at a concentration of 50%, and in the unplanted unit, the rest period of 30 days was applied. The efficiencies of the unclogging methods were evaluated by solids analysis, hydraulic conductivity tests, drainable porosity and tests with tracers. The unclogging methods applied in the beds were not effective to return with the hydraulic, hydrodynamic and performance conditions of the system. The volume of hydrogen peroxide applied to the planted unit had little effect, with the largest portion of the product being consumed by the sludge accumulated on the bed surface. In the unplanted unit, the rest period was also not effective. The high degree of clogging of the units requires more invasive methods or higher volumes of oxidizing chemicals.